The Relationship Between Quality Factors and Online Education Satisfaction: The Moderating Role of Communication Quality in Shanghai, China - Fei, Hu; Tahir, Suhaidah Binti (South Asian Journal of Social Sciences and Humanities, 2024)
Purpose: The rapid advancement and technology have turned every page of life and have  primarily affected the student life and education domain. Since COVID pandemic, the  education sector embraced the online medium and tried its best effort to effectively continue  the learning stream and to evaluate the student satisfaction with the online education system,  this study developed an empirical model framing the impact of interactivity, course  availability and learning style on the student satisfaction with the catalytic role of cognitive  engagement and the external role of communication quality. Method: The study was  conducted in the education sector and students who use online platforms and learning  materials were targeted within the boundaries of China and the sample size was decided  according to item response theory i.e., 440. The SPSS and Amos were used for data analysis. Findings: The findings revealed the significant effects of all the direct and indirect effects  and moderation was also accepted for the course availability and interactivity. Conclusion: This research examines the complex interplay between quality metrics, communication  quality, and overall satisfaction among online learners to develop a deeper understanding of  satisfaction in digital education. The study highlights the impact of three key quality factors  on happiness in online learning contexts: interactivity, course accessibility, and learning  preferences. It focuses on unraveling how these variables relate to and influence each other as  well as learner contentment in virtual classrooms.
Keywords: Online education satisfaction; Communication quality; interactivity; course availability; Learning style